KAJIAN STRUKTURAL DAN MITOLOGI DALAM WAWACAN SULANJANA - R. Desriani; Fajar S.M (Prodi Pendidikan Bahasa dan Sastra Daerah, 2018)
This study has the aim to describe all the structures and mythology that appear in the story Wawacan Sulanjana. The method used in this research is descriptive by analyzing the data. As well as the technique of collecting data in this research is by filling out the data card. In the process of research, found things that appear in Wawacan Sulanjana, including mythology and structure, while the structure is a Guru Wilangan, Guru Lagu, characteristics of pupuh, sasmita of pupuh, themes, plots, characters, background places, background ambience, timescapes , point of view, style, symbols, irony and its mythology. The results of the analysis and description collected 8 benchmark of pupuh, including Asmarandana cantos, Sinom, Kinanti, pickaxe, Dangdanggula, Mijil, Durma, and Magatru. In general, the theme of his talks about Dewi Sri Pohaci or DEWI and Sulanjana, found 19 figures, two main characters, 10 of the second character, and 7 additional actors, 21 lanes found that groove forward. And there are 26 settings, including background 9 places, 4 setting time, and 13 background ambience. Viewing angles are used is the third person is not limited. Style of language used in this study is hyperbole and personification, 3 symbols, and found the irony of the beginning of the story until the end of the story. Wawacan Sulanjana mythology is one of the main wawacan discussing the birth of Dewi Sri and History of Rice. In the story this wawacan considerations about the crops are plants such as rice, glutinous rice, etc. Researchers hope to further research in order to conduct further research. Finally, hopefully this research can increase knowledge of the language, literature and culture of Sunda.